The Relationship Between the Role of Midwives in Home Care Services PMT Provision with the Nutritional Status of Toddlers in the Work Area of the Sawah Lebar Community Health Center Bengkulu City - Erpina Erpina; Bella Anarkie; Febra Ayudiah (Student Scientific Journal, 2026)
According to the World Health Organization (WHO, 2023), immunization is a highly Based on global data, UNICEF (2025) estimates that approximately 184 million children under 19 years of age are undernourished, with approximately 150 million children under five experiencing stunting and 43 million children experiencing wasting. Although various countries have implemented nutritional interventions, the prevalence of undernourished children remains a challenge in many regions, particularly in developing countries. The purpose of this study was to determine the relationship between the role of midwives in home care services and PMT provision and the nutritional status of toddlers in the Sawah Lebar Community Health Center (Puskesmas) working area of Bengkulu City. The study used a cross-sectional design, and data were collected by distributing questionnaires to 75 mothers with toddlers aged 0-59 months in the Sawah Lebar Community Health Center working area of Bengkulu City using a simple random sampling technique. Univariate analysis results showed that nearly half of the respondents, 28 (37.3%) in the Sawah Lebar Community Health Center (Puskesmas) work area in Bengkulu City, reported that midwives played an inadequate role in home care services and assisted with PMT provision. Some respondents, 40 (53.3%) in the Sawah Lebar Community Health Center work area in Bengkulu City, reported good nutritional status. Bivariate analysis results showed a significant relationship between the role of midwives in home care services and assisted with PMT provision and the nutritional status of toddlers in the Sawah Lebar Community Health Center work area in Bengkulu City, with a p-value of 0.003. Health workers should improve their role in home care services and assisted with PMT provision through regular home visits, monitoring toddler nutritional status, and providing easily understood nutrition education that involves families to prevent both undernutrition and overnutrition.